Analisis Kesalahan Penulisan Bahasa Indonesia Pada Skripsi Mahasiswa S1 - Louis Armando Tarigan; Nini Suryani Nini Suryani Nini Suryani; Switri Ramadhani Siregar; Muhammad Surip (CV. Alim's Publishing, 2024)
This research evaluates errors in the use of Indonesian in non-Indonesian language and literature students' theses, focusing on aspects of spelling, punctuation, use of italics, and writing particles or affixes. Qualitative descriptive methods are used for in-depth text analysis, identifying language errors in various linguistic fields. The findings show that errors in the use of punctuation marks, especially periods and commas, are dominant with percentages of 53.06% and 38.78% respectively. Spelling errors, especially in the affixes